2016
DOI: 10.1039/c5ra25765d
|View full text |Cite
|
Sign up to set email alerts
|

Research on controllable degradation of sulfonylurea herbicides

Abstract: Through studying structure, bioassay and soil degradation tri-factor relationship, potential controllable degradation of SU was firstly explored and summarized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…The structure of 5-substituted chlorsulfuron compounds is shown in Figure 2. The synthetic procedure of 5-dialkylamino-substituted compounds is shown in Figure 3, which was reported in our previous papers [11][12][13]. The synthetic procedure of 5-dialkylamino-substituted compounds is shown in Figure 3, which was reported in our previous papers [11][12][13].…”
Section: Compounds Nl101-nl108mentioning
confidence: 72%
See 3 more Smart Citations
“…The structure of 5-substituted chlorsulfuron compounds is shown in Figure 2. The synthetic procedure of 5-dialkylamino-substituted compounds is shown in Figure 3, which was reported in our previous papers [11][12][13]. The synthetic procedure of 5-dialkylamino-substituted compounds is shown in Figure 3, which was reported in our previous papers [11][12][13].…”
Section: Compounds Nl101-nl108mentioning
confidence: 72%
“…The synthetic procedure of 5-dialkylamino-substituted compounds is shown in Figure 3 , which was reported in our previous papers [ 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group has been working on the problem of the long degradation times of sulfonylurea herbicides. In our previous study, we found that the 5th substituted groups on the benzene ring in chlorsulfuron has a great influence on its degradation rate in acidic soils and concluded for the first time that electron-donating substituents could accelerate degradation rates in acidic soil ( Figure 1 ) [ 11 , 12 ]. Li et al found that 5-dialkylamino-substituted groups on the benzene ring of chlorsulfuron could greatly accelerate degradation under alkaline conditions [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%